Teaching Multiplication with Regrouping Using the Concrete-representational-abstract Sequence and the Strategic Instruction Model - Flores, Margaret M.; Franklin, Toni M. (Journal of the American Academy of Special Education Professionals, 2014)
The Common Core State Standards (2010) involve the demonstration of conceptual knowledge of numbers and operations. For students who struggle with mathematics and have not responded to instruction, it is important that interventions emphasize this understanding. In order to address conceptual understanding of numbers and operations in meeting the rigorous Common Core State Standards, interventions should include the use of explicit instruction, manipulation of objects, and visual representation of numbers. The current pilot study investigated the use of such a method within a tiered intervention model, the concrete-representational-abstract (CRA) sequence and the strategic Instruction Model (SIM). Six fourth grade students receiving intervention through a response to intervention model participated. Multiplication with regrouping was taught using CRA and SIM (CRA-SIM) over the course of ten lessons as part of an intervention period. Data were collected before and after CRA-SIM instruction and statistical analysis showed that students made significant gains after instruction. The practical implications and application of CRA-SIM instruction will be discussed.